1992
DOI: 10.1073/pnas.89.22.10945
|View full text |Cite
|
Sign up to set email alerts
|

Induction of calcium-independent nitric oxide synthase activity in primary rat glial cultures.

Abstract: Exposure of primary cultures of neonatal rat cortical astrocytes to bacterial lipopolysaccharide (LPS) results in the appearance of nitric oxide synthase (NOS) activity. The induction of NOS, which is blocked by actinomycin D, is directly related to the duration of exposure and dose of LPS, and a 2-hr pulse can induce enzyme activity. Cytosol from LPS-treated astrocyte cultures, but not from control cultures, produces a Ca2+-independent conversion of L-arinine to L-Citrulline that can be completely blocked by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
305
7
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(332 citation statements)
references
References 32 publications
16
305
7
4
Order By: Relevance
“…Primary astrocyte cultures (RNB cells) were prepared from the cerebral cortex of 1-day-old neonatal rats as described previously (Galea et al, 1992;Kondo et al, 1996). RNB cells were maintained in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum, 4 mM glutamine, 100 U/ml penicillin, and 100 mg/ml streptomycin (Invitrogen, Carlsbad, CA, USA).…”
Section: Cell Culturementioning
confidence: 99%
“…Primary astrocyte cultures (RNB cells) were prepared from the cerebral cortex of 1-day-old neonatal rats as described previously (Galea et al, 1992;Kondo et al, 1996). RNB cells were maintained in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum, 4 mM glutamine, 100 U/ml penicillin, and 100 mg/ml streptomycin (Invitrogen, Carlsbad, CA, USA).…”
Section: Cell Culturementioning
confidence: 99%
“…Inflammatory mediators induce NOS-2 expression in astrocyte cultures in vitro (Galea et al 1992;Hewett et al 1993;Simmons and Murphy 1992) Paradoxically, transforming growth factor-β1 (TGFβ1), a cytokine with anti-inflammatory properties, enhanced NO production from astrocytes treated with LPS plus IFNγ and this correlated with a 6-fold increase in the fraction of cells that expressed NOS-2 protein . Since TGFβ1 alone did not induce NOS-2, this suggested that TGFβ1 enabled additional astrocytes to respond to LPS plus IFNγ.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Inflammatory mediators induce NOS-2 expression in astrocyte cultures in vitro (Galea et al 1992;Hewett et al 1993;Simmons and Murphy 1992) and NOS-2 has been detected in astrocytes in several CNS inflammatory conditions in vivo, including cerebral ischemia and Alzheimer and Parkinson diseases (Acarin et al 2002;Endoh et al 1994;Garcion et al 1998;Katsuse et al 2003;Kwak et al 2005;Luth et al 2002). Importantly, NO from glial NOS-2 has been shown to disrupt the blood-brain barrier (Boveri et al 2006) and promote or exacerbate excitotoxic neuronal cell death Hewett et al 1994;Hewett et al 1996;Vidwans and Hewett 2004), an underlying cause of neuropathology in several neurological diseases (Choi 1988;Coyle and Puttfarcken 1993;Meldrum and Garthwaite 1990).…”
mentioning
confidence: 99%
“…The expression and activity of the latter are induced by inflammatory stimuli, independent of the cytosolic calcium concentration. 5 In the citrulline-NO cycle, argininosuccinate synthase (ASS) activity is rate-limiting with regard to the supply of L-arginine as substrate for NOS. ASS is an ubiquitous enzyme that is expressed in all tissues, including the brain.…”
Section: Introductionmentioning
confidence: 99%